Profile of Science Processing Skill Primary Teacher Education Students in Simulation of Science Learning Media in Online Learning Period - Asri Widia Ningrum; Banu Setyo Adi; Ikhlasul Ardi Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2022)
Online learning due to the COVID-19 pandemic impacts the university level, especially during the learning process. This influence was felt by PGSD students at Yogyakarta State University when simulating online learning media. The simulation of learning media is undoubtedly related to students' science process skills as a provision for prospective teachers. These science process skills must be measured as preparation for becoming a prospective teacher in the learning process in the future. However, detailed measurements have not been carried out. Therefore, this study aims to describe the science process skills of PGSD students in simulating science learning media in a network. The method used in this research is qualitative with a descriptive qualitative approach with data collection techniques using observation and interviews. The data analysis technique uses Miles, Huberman Saldana, which consists of condensing the data, presenting the data and drawing conclusions. The results of this study are the indicators observing 83.33% very high category, classifying 44.44% moderate category, interpreting 33.33% low category, predicting 50.00% sufficient category, asking questions 50.00% sufficient category, formulating hypotheses 50.00% sufficient category, planning an experiment 77.78% high category, using tools and materials 11.11% deficient category, apply the concept of 61.11% high category and communicate 61.11% high category. In general, students' science process skills have not been able to optimally, so there is a need for a lecture program to simulate science learning media on a network by providing PhET simulation media.